2011
DOI: 10.1111/j.1537-2995.2011.03362.x
|View full text |Cite
|
Sign up to set email alerts
|

Report of the first nationally implemented clinical routine screening for fetal RHD in D− pregnant women to ascertain the requirement for antenatal RhD prophylaxis

Abstract: These data represent the first demonstration of the reliability of routine antenatal fetal RHD screening in D-, pregnant women to ascertain the requirement for antenatal RhD prophylaxis. Our findings should encourage the implementation of such screening programs worldwide, to reduce the unnecessary use of RhIG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
162
1
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(177 citation statements)
references
References 25 publications
8
162
1
6
Order By: Relevance
“…For example, Banch Clausen et al 20 stated that the challenges to the implementation of the prenatal RhD screening programme were related to programme anti-D prophylaxis compliance. Another study by Banch Clausen et al 24 noted that there may be challenges in logistics concerning the transportation of samples from remote sites to testing laboratories and in getting results back to the correct general practitioner.…”
Section: Results Of Implementation Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Banch Clausen et al 20 stated that the challenges to the implementation of the prenatal RhD screening programme were related to programme anti-D prophylaxis compliance. Another study by Banch Clausen et al 24 noted that there may be challenges in logistics concerning the transportation of samples from remote sites to testing laboratories and in getting results back to the correct general practitioner.…”
Section: Results Of Implementation Studiesmentioning
confidence: 99%
“…This study also stated that continued use of anti-D in women who can be shown to have RhD-negative fetuses may be unethical. Banch Clausen et al 24 recommended continuing cord blood typing in practice to ensure that postnatal anti-D is given if NIPT compliance is poor. Damkjaer et al 27 suggested improvement in relevant knowledge on prenatal RhD screening among general practitioners and midwives in Denmark.…”
Section: Results Of Implementation Studiesmentioning
confidence: 99%
See 3 more Smart Citations